Rádio escolar: práticas de letramento na Educação de Jovens e Adultos - Magna Angélica Oliveira Rodrigues (2021)
This research aims to develop, through school radio insertion, computers, and smartphones, literacy practices that potentializes discursive skills as well as promotes multiple speaking abilities and digital literacy in the Education of Young and Adults program of Elementary Schools students (EJA - Educação de Jovens e Adultos). This is a qualitative and propositional research, which aims to elaborate a school radio project and literacy practices to be used with EJA night school students. Through this methods means, critical reading and creative production of written and spoken texts will be stimulated, under a theoretical- methodological view of written and oral genres researchs, based on radiophonic genres program schedules studies and playlists, and journalistic genre radio interviews. It is expected that those genres will help consolidate and/or broaden reading competencies, interpretation, and text production in different languages (oral and written) and within specific genres, situating them inside their production conditions. Aforementioned, with the purpose that the participating students will be able to read, interpret and write, becoming enabled to fight for a more worthy life, to act critical, reflexively, and autonomously, contributing to a more equal society.